Long-term maxillary three dimensional changes following maxillary protraction with or without expansion: A systematic review and meta-analysis - Wei-Cheng Lee; Yi-Shing Shieh; Yu-Fang Liao; Cho-Hao Lee; Chiung Shing Huang (Elsevier, 2021)
Background/purpose: Maxillary protraction with or without expansion appears to be an effective orthopedic treatment in skeletal class III growing patients, but the long-term effect on maxilla changes is less clear. The aim of this meta-analysis was to evaluate long-term three dimensional skeletal effects on maxilla through face mask (FM) with or without rapid maxillary expansion (RME) in skeletal CIII growing patients. Materials and methods: We searched database including PubMed, Science Direct, Embase and Web of Science through Feb 2020. Inclusion criteria were randomized controlled trials or cohort studies recruiting growing patients who received maxillary protraction and/or expansion and comparing the treatment groups with untreated controls. The follow-up periods were more than 3 years. Risk of bias was assessed using the Cochrane tools (RoB2.0 and ROBINS-I). GRADE was used to qualify the evidence. Results: This meta-analysis included 6 studies comprising 327 participants in total. No statistically significant changes were observed on the degree of Sella-Nasion-A point (SNA) in the treated groups when compared with the untreated controls. However, significant increase on maxillary rotation degree (mean difference: 8.20, 95% CI = 6.87-9.53, p < 0.001) and maxillary base width (mean difference: 2.27, 95% CI = 1.39-3.15, p < 0.001) in the treated groups, if compared with untreated controls. Conclusion: Our results indicated that FM and FM/RME treatments might not be long-term effective on correcting maxillary anteroposterior hypoplasia in growing patients. Additionally, more long-term studies are still necessary to further assess its skeletal benefits on maxilla in vertical and transverse dimension.